APPLICATION OF THE SOFTWARE PACKAGE LTSPICE FOR DESIGNING AND ANALYSING THE OPERATION OF ELECTRONIC SYSTEMS - Ptak, Paweł (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper presents application of the software package LTspice in the teaching of designing and analysis of electronic systems operation. The program has been used for simulating the operation of typical electronic systems, such as filters. The systems created in the simulation can provide a basis for preparing students to participate in laboratory classes. The results obtained in a simulation can be subsequently verified by testing real systems during the electronics laboratory classes. The results of simulation and real experiments can also be compared and utilised for making an analysis and writing a report on the experiment.